2016
DOI: 10.3390/sym8040018
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Rate of a Stable, Monotone and Consistent Scheme for the Monge-Ampère Equation

Abstract: Abstract:We prove a rate of convergence for smooth solutions of the Monge-Ampère equation of a stable, monotone and consistent discretization. We consider the Monge-Ampère equation with a small low order perturbation. With such a perturbation, we can prove uniqueness of a solution to the discrete problem and stability of the discrete solution. The discretization considered is then known to converge to the viscosity solution but no rate of convergence was known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Awanou [2] proved a linear rate of convergence for classical solutions for the widestencil method, when applied to a perturbed Monge-Ampère equation with an extra lower order term δu; the parameter δ > 0 is independent of the mesh and appears in reciprocal form in the rate. In contrast, our analysis hinges on the discrete comparison principle and two discrete barrier functions, which are instrumental in proving convergence to the viscosity solution of (1.1).…”
Section: Introductionmentioning
confidence: 99%
“…Awanou [2] proved a linear rate of convergence for classical solutions for the widestencil method, when applied to a perturbed Monge-Ampère equation with an extra lower order term δu; the parameter δ > 0 is independent of the mesh and appears in reciprocal form in the rate. In contrast, our analysis hinges on the discrete comparison principle and two discrete barrier functions, which are instrumental in proving convergence to the viscosity solution of (1.1).…”
Section: Introductionmentioning
confidence: 99%
“…Error estimates in H 1 (Ω) are established in [3,4] for solutions with H 3 (Ω) regularity or more. Awanou [1] also proved a linear rate of convergence for classical solutions for the wide-stencil method, when applied to a perturbed Monge-Ampère equation with an extra lower order term δu; the parameter δ > 0 is independent of the mesh and appears in reciprocal form in the rate.…”
Section: Introductionmentioning
confidence: 94%
“…Since the operator M + s is pointwise consistent and convergence to viscosity solution is point by point, we do not discuss linear interpolation. It can be shown that for smooth solutions [2], it leads to a convergence rate O(h + dθ) where dθ is called directional resolution and dθ → 0 as h → 0.…”
Section: Monotone Schemes Let Us Denote Bymentioning
confidence: 99%